Judicial Discretion and the Limits of Homologation in Cross-Border Insolvency: Rethinking Legal Certainty and Creditor Protection from a Comparative Perspective - Reinhard R. S, Andra; Hasibuan, Fauzie Yusuf; Rangsimanop, Pattharawadee (Journal Evidence Of Law, 2025)
This article examines the relationship between judicial discretion and homologation procedures in bankruptcy law, highlighting their impact on legal certainty and creditor protection across different legal systems. Through a comparative legal approach to Indonesia, the United States, and the Netherlands, this study demonstrates that judicial discretion that is not normatively constrained, particularly in developing jurisdictions, has the potential to erode procedural predictability and lead to disparities in the treatment of creditors. Conversely, systems that adopt a parameter-based judicial discretion structure and procedural transparency, such as in the US and the Netherlands, are capable of producing fairer and more predictable bankruptcy rulings. Using a framework of reflective legal theory and social systems theory, this study offers a normative design to harmonize homologation procedural standards without eliminating judicial flexibility. This study contributes not only to the development of bankruptcy law theory but also to national legal policy reform in the context of harmonization with international best practices, particularly within the UNCITRAL framework.